2014
DOI: 10.1590/s0103-84782014000200010
|View full text |Cite
|
Sign up to set email alerts
|

Ideal seeds harvest moment of different maize hybrids

Abstract: The aim of this study was to identify the ideal maize seed harvest moment by different characteristics, as black layer

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 14 publications
(21 reference statements)
2
9
0
Order By: Relevance
“…2 and Table 3). A similar stage for achieving maximum SG and CTG has also been observed in previous work, while it was observed that obtaining the maximum AAG took several days longer 10 . The different dates to achieve maximum SG and AAG might result from the different genotypes used in these studies.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…2 and Table 3). A similar stage for achieving maximum SG and CTG has also been observed in previous work, while it was observed that obtaining the maximum AAG took several days longer 10 . The different dates to achieve maximum SG and AAG might result from the different genotypes used in these studies.…”
Section: Discussionsupporting
confidence: 86%
“…SG, CTG and AAG are the three most important indexes to predict seed quality 4 . Previous investigations found that maize seed quality could be greatly influenced by the percentage of seed maturity, which is greatly affected by different harvest times 10,20 . However, most investigations only used SG as a seed vigor index and seldom comparisons of seed maturity to CTG and AAG vigor could be addressed, except that TeKrony and Hunter conducted the CTG test and Junior et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The relationship between the maturity length of a maize hybrid and its GDD accumulations at a given location determine their optimal harvesting period and its adaptability. Intensively studies have been carried out on the effect of harvesting stages on maize yield and agreed that the optimal time to harvest maize is when close to its physiological maturity (Daynard, 1972;Henning et al, 2011;Jacob Junior et al, 2014). However, consideration was not even under extreme or adverse weather conditions which may prevent the crop from attaining physiological maturity.…”
Section: Introductionmentioning
confidence: 99%